2011
DOI: 10.1002/ar.21402
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Exposure of Rats to Antidepressants Affects Behavioral Reactions to Novelty and Social Interactions in a Manner Analogous to Autistic Spectrum Disorders

Abstract: We have demonstrated that neonatal exposure to selective serotonin reuptake inhibitors has lasting effects on behavior and serotonergic neurons in Long Evans rats. Hyperserotoninemia and altered sensory processing are reported in autistic spectrum disorders (ASD). We hypothesized that early life exposure to SSRIs alters sensory processing, disrupts responses to novelty and impairs social interactions in a manner similar to that observed in ASD. Male and female Long-Evans rat pups were administered citalopram, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 35 publications
(41 reference statements)
13
84
0
Order By: Relevance
“…Although we do not suggest that the juvenile play behavior that we assess corresponds to a specific trait dimension of ASD, our findings are consistent with the possibility that dysregulation/dysfunction of the 5-HT system during early brain development may be the critical contributing factor in the etiology of ASD. This notion is also supported by the fact that the altered behaviors were observed in CTM-exposed rats but not in non-SSRI perinatally exposed animals (29,41), implicating a potential 5-HT linkage of social dysfunctioning seen in ASD (42).…”
Section: Discussionmentioning
confidence: 73%
“…Although we do not suggest that the juvenile play behavior that we assess corresponds to a specific trait dimension of ASD, our findings are consistent with the possibility that dysregulation/dysfunction of the 5-HT system during early brain development may be the critical contributing factor in the etiology of ASD. This notion is also supported by the fact that the altered behaviors were observed in CTM-exposed rats but not in non-SSRI perinatally exposed animals (29,41), implicating a potential 5-HT linkage of social dysfunctioning seen in ASD (42).…”
Section: Discussionmentioning
confidence: 73%
“…Though few studies have examined whether early FLX exposure affects social behaviours in rodents, the findings of those that have suggest these behaviours may be impaired. Aspects of social play are reduced considerably in male, but not female, adolescent rats following postnatal exposure to FLX [52]. Similar effects on the social play of male adolescent rats have also been observed following prenatal exposure [11], suggesting that this effect is consistent regardless of the period of exposure.…”
Section: Long-term Behavioural Outcomesmentioning
confidence: 81%
“…In adolescence, early exposure inhibits locomotion [23,41,50,51] and decreases novel object exploration [52]. Lisboa et al [35] observed decreased locomotion only in male mice, suggesting a difference in sensitivity between the sexes.…”
Section: Long-term Behavioural Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early antidepressant exposure in male rats results in long lasting behavioral effects, as well as a reduction in expression of the 5-HT synthetic enzyme (tryptophan hydroxylase) within the raphe nuclear complex and of the 5-HT transporter (SERT) within their cortical efferent fibers (Mirmiran et al, 1981; Maciag et al, 2006; Iniguez et al, 2010; Oberlander et al, 2009; Weaver et al, 2010, Rodriguez-Porcel et al, in press). In a recent study of adolescent (postnatal day-PN45) rats exposed to a SSRI, West et al (2010) reported that brief (2 or 4 days) treatment increased LC neuronal activity, suggesting an opposite effect compared to adult treatment.…”
Section: Introductionmentioning
confidence: 99%